Mastering clean code in JavaScript - Loukas, Dimitris (Packt Publishing, 2018)
"In this course, you will learn various concepts and techniques, essential principles, patterns, and practices for writing clean code in JavaScript. You will be introduced to some general guidelines on how to better structure your JavaScript code. You will then learn about clean code best practices while working with variables, functions objects, and the latest ES6 classes. Next, you will discover functional programming, how to write pure functions, and how to use built-in functional methods. You will then move on to modular JavaScript and explore the various ways you can structure your modules. After that, you will master various design patterns and programming principles. Unit testing is very important and you will learn to do this with Jasmine and Karma, to make handling errors easy. By the end of the course, you will have learned to learn clean coding with functional programming, explored various modules in JavaScript, and designed patterns and principles. Overall you will learn to write better code with improved readability."--Resource description page